2017
DOI: 10.7754/clin.lab.2016.160305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of In Vitro Hemolysis on 80 Different Laboratory Tests

Abstract: Hemolysis is a common problem for accuracy in many routine laboratory tests. Although the quantitative effects of hemolysis can only be roughly estimated in this report, the approximate extent of change in specific laboratory tests is useful for establishing a baseline for future hemolytic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
13
2
Order By: Relevance
“…Therefore, it may be related to false-positive TRAb levels. In addition, hemolysis has been reported to affect electrochemiluminescence immunoassays, which are used in third-generation TRAb test [24][25][26]. Thus, false-positive TRAb levels may also be attributed to cell-free hemoglobin in plasma, even though severe hemolysis was not found in the plasma samples used in the current report.…”
Section: Discussionmentioning
confidence: 39%
“…Therefore, it may be related to false-positive TRAb levels. In addition, hemolysis has been reported to affect electrochemiluminescence immunoassays, which are used in third-generation TRAb test [24][25][26]. Thus, false-positive TRAb levels may also be attributed to cell-free hemoglobin in plasma, even though severe hemolysis was not found in the plasma samples used in the current report.…”
Section: Discussionmentioning
confidence: 39%
“…In the clinical laboratory, hemolysis interferes with the measurement of multiple biomarkers [12][13][14][15] for the following main reasons. First, the released intracellular substances from blood cells impact the progress of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…As a key mediator of classic IgE-mediated anaphylaxis, IgE is often used as one of the indicators for the diagnosis of anaphylactic diseases in both clinical and forensic medicine [11]. Clinical studies have demonstrated that hemolysis interferes with the measurement of multiple indicators and that hemolyzed samples are not suitable for biochemical analysis in clinical laboratories [12][13][14][15]. However, in forensic practice, blood samples always suffer from irreversible hemolysis due to postmortem changes, even within a short postmortem interval (PMI) [16], which induces unavailable or unsuitable serum for postmortem biochemical analysis of IgE.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, hemolysis blood sample may affect the measurement of many tests, such as serum potassium, NSE and lactate dehydrogenase (LDH), etc The hemolytic samples can be regarded as unqualified specimens and rejected. The visible hemolysis samples can be identified by machine or naked eyes easily, but if slight hemolysis could not be identified, erroneous results may lead to wrong clinical decisions.…”
Section: Discussionmentioning
confidence: 99%